Improved spatial memory for physical versus virtual navigation - Maidenbaum, Shachar; Kremen, Vaclav; Sladky, Vladimir; Miller, Kai; Gompel, Jamie Van; Worrell, Gregory A; Jacobs, Joshua (Journal of neural engineering, 2025)
Objective. Virtual reality (VR) has become a key tool for researching spatial memory. Virtual environments offer many advantages for research in terms of logistics, neuroimaging compatibility etc. However, it is well established in animal models that the lack of physical movement in VR impairs some neural representations of space, and this is considered likely to be true in humans as well. Furthermore, it is unclear how big the disruptive effect stationary navigation is-how much does physical movement during encoding and recall affect human spatial memory and representations of space? What effect does the fatigue of actually walking during tasks have on participants-will physical movement decrease performance, or increase perception of difficulty?Approach. We utilize Augmented reality (AR) to enable participants to perform a spatial memory task while physically moving in the real world, compared to a matched VR task performed while stationary. Our task was performed by a group of healthy participants, by a group of stationary epilepsy patients, as they represent the population from which invasive human spatial signals are typically collected, and, in a case study, by a mobile epilepsy patient with an investigational chronic neural implant (Medtronic Summit RC + STM) streaming real-time continuous hippocampal local field potential data.Main results. Participants showed good performance in both conditions, but reported that the walking condition was significantly easier, more immersive, and more fun than the stationary condition. Importantly, memory performance was significantly better in walking vs. stationary in all groups, including epilepsy patients. We also found evidence for an increase in the amplitude of the theta oscillations associated with movement during the walking condition.Significance. Our findings highlight the importance of paradigms that include physical movement and suggest that integrating AR with movement in real environments can lead to improved techniques for spatial memory research.
Keywords: Spatial Memory; Humans; lidé středního věku; Spatial Navigation; augmentovaná realita; Female; mladý dospělý; dospělí; lidé; Virtual Reality; virtual reality; Augmented Reality; chůze; Adult; augmented reality; ženské pohlaví; Male; Middle Aged; virtuální realita; Young Adult; Walking; navigation; prostorová navigace; prostorová paměť; physical movement; mužské pohlaví; spatial memory